Functional Role of VCAM-1 Targeted Flavonoid-Loaded Lipid Nanoemulsions in Reducing Endothelium Inflammation - Elena Valeria Fuior; Mariana Deleanu; Cristina Ana Constantinescu; Daniela Rebleanu; Geanina Voicu; Maya Simionescu; Manuela Calin (MDPI AG, 2019)
Citrus flavonoids have well-documented protective effects on cardiovascular system, but the poor water solubility and reduced bioavailability restrict their therapeutic use. We aimed to overcome these limitations and encapsulated naringenin and hesperetin into lipid nanoemulsions (LNs), targeted to vascular cell adhesion molecule-1 (VCAM-1), which is expressed on activated endothelial cells (ECs). LNs were characterized by a hydrodynamic size of ~200 nm, negative zeta potential, an encapsulation efficiency of flavonoids higher than 80%, good in vitro stability and steady release of the cargo. The LNs were neither cytotoxic to human ECs line EA.hy926, nor provoked in vitro lysis of murine erithrocytes. Then, we tested whether these nanoformulations reduce tumor necrosis factor-alpha (TNF-α) induced EC-activation. We found that flavonoid-loaded LNs, either non-targeted or targeted to the endothelium, were taken up by the EA.hy926 cells in a dose-dependent manner, but dependent on TNF-α only in the case of endothelium-targeted LNs. Moreover, these nanoparticles inhibited both the adhesion and transmigration of THP-1 monocytes on/through activated ECs, by mechanisms involving a reduced expression of the pro-inflammatory chemokine monocyte chemotactic protein 1 (MCP-1) and diminished nuclear translocation of nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB).